ASME 2010 3rd Joint US-European Fluids Engineering Summer Meeting: Volume 2, Fora 2010
DOI: 10.1115/fedsm-icnmm2010-30527
|View full text |Cite
|
Sign up to set email alerts
|

Novel 4-Stage Traveling Wave Thermoacoustic Power Generator

Abstract: Utilizing low temperature differences from solar vacuum tube collectors or waste heat in the range 70–200 °C seems to be the most promising and commercial interesting field of applications for thermoacoustic systems. Recently a novel 4-stage “self matching” traveling wave engine is developed and tested. Beside the low acoustic loss and compactness, due to traveling wave feedback, all components per stage are identical which is beneficial from (mass) production point of view. Based on this concept a 100 kWT the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 3 publications
2
67
0
Order By: Relevance
“…Biwa et al 9) indicated that the use of multiple regenerators offers an easy and effective method of decreasing the onset temperature. De Blok 10) suggested a thermoacoustic system with a multistage PM with an expanded diameter to decrease the onset temperature. Shibata et al 11) succeeded in decreasing the onset temperature to be lower than that of a system with a uniform inner diameter by making a step-shape system.…”
Section: Introductionmentioning
confidence: 99%
“…Biwa et al 9) indicated that the use of multiple regenerators offers an easy and effective method of decreasing the onset temperature. De Blok 10) suggested a thermoacoustic system with a multistage PM with an expanded diameter to decrease the onset temperature. Shibata et al 11) succeeded in decreasing the onset temperature to be lower than that of a system with a uniform inner diameter by making a step-shape system.…”
Section: Introductionmentioning
confidence: 99%
“…De Blok made a series of efforts to develop various travelling wave thermoacoustic engines [1,[7][8][9]. He proposed a traveling-wave thermoacoustic engine with coaxial configuration in 3 traveling wave thermoacoustic electric generator based on a flexure-bearing linear alternator for deep space application.…”
Section: Introductionmentioning
confidence: 99%
“…9 The designed travelling-wave thermoacoustic engine with a feedback pipe (FBP) could start at a temperature difference of only 65 K. Recently, a multi-stage version of this type of engine was able to start at a temperature difference of only 40 K at each stage. 18 The acoustic power generated by the thermoacoustic engines from the heat input can be utilized in different ways. In general, it can be used for two main purposes: one is to directly convert the acoustic power to electricity through an electro-dynamic transduction mechanism; the other is to drive coolers or heat pumps, 5 which can be either thermoacoustic coolers (heat pumps) or pulsed-tube coolers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…56 This arrangement has also the advantage of utilising low-grade heat source with a lower temperature difference across each stage. 9,18 The prototype uses air at two bar as the working gas and a commercially available high power woofer as an alternator. A schematic drawing of the prototype is shown in Figure 21a.…”
Section: Current and Future Workmentioning
confidence: 99%